Analyzing Key Categories in the Literature of Contemporary Iranian Architecture; 1946 – 2016 - حمیدرضا پیشوائی; زهرا میرزائی; سینا زارعی حاجی‌آبادی (صفه, 2020)
It has been about 70 years since Persian literature has emerged on contemporary Iranian architecture. This research investigates the key categories of this literature, with a focus on the most recurring categories discussed between 1946 and 2016. To achieve this, 389 of the most important sources on this topic are selected, and their key categories are identified. Finally, based on the 37 most recurring categories, under nine general sets, these texts are analyzed qualitatively. The main sets are about the relationship between contemporary and past architecture, architects, concepts and contexts, normative statements, the relationship between contemporary Iranian and world architecture, the ways of discussing architectural works, periods, the ways of discussing history, and modernity. The results of this analysis indicate that the works of architecture, architects, historical narratives, and architectural pathology are the most recurring themes in the past 70 years. Categories such as works of architecture and architects have continuously attracted the attention of authors architecture and architects have; however, some other categories, such as architectural pathology and historical narratives, have recently taken centre stage.